2018
DOI: 10.33805/2576-8484.142
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Parents-Adolescents Communication on Sexual and Reproductive Health Matters between Evelyn Hone College Lecturers and their Adolescent Children, Lusaka, Zambia

Abstract: Background: One of the neglected issues in our society today, is effective communication between parents and adolescents on matters of Sex and Reproductive Health. This problem has saliently exposed the adolescents to the risk of contracting Sexually Transmitted Infections (STIs) and teenage pregnancies as well as engaging in drug and substance abuse. As such, this study aimed at assessing the extent of parent-adolescents communication on Sexual and Reproductive Health (SRH) matters among the Lecturers at Evel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This study showed that 56.3% of adolescents who participated in the study had communicated with their parents. This result wa slower than studies conducted in USA (Widman et al , 2014), Ghana (Esantsi et al , 2015) and Zambia (Haakonde et al , 2018). The reason may be associated with differences in culture, socioeconomic development and studied populations, whereby the study in Zambia included adolescents of highly educated families.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This study showed that 56.3% of adolescents who participated in the study had communicated with their parents. This result wa slower than studies conducted in USA (Widman et al , 2014), Ghana (Esantsi et al , 2015) and Zambia (Haakonde et al , 2018). The reason may be associated with differences in culture, socioeconomic development and studied populations, whereby the study in Zambia included adolescents of highly educated families.…”
Section: Discussionmentioning
confidence: 61%
“…PAC on SRH issues varies across and within countries. It reached to 71% in USA (Widman et al , 2014), 21% in Tanzania (Muthengi et al , 2015), 9.5% in Nigeria (Ojebuyi et al , 2019), 90% in Zambia (Haakonde et al , 2018), 61% in Ghana (Esantsi et al , 2015) and 19% in Rwanda (Bushaija et al , 2013). In Ethiopia, PAC on SRH matters among secondary and preparatory school students varied by setups like 47% Oromia (Habte et al , 2019), 28.9% in BenishangulGumuz (Yesus and Fantahun, 2010), 68.5% (Mekie et al , 2019) and 82.7% in Amhara region (Chane and Cherie, 2018).…”
Section: Introductionmentioning
confidence: 99%